El turismo activo como modalidad turística en expansión. Análisis de la oferta de turismo activo en España - Araújo Vila, Noelia (2012)
Parallel to the social and economic situation, where the experience economy is a reality, new tourist typologies are emerging in line with this demand experiential. Tourists are looking for sensations and emotions, so tourism sector has diversified its offer adapting to this desire. Active tourism appears, mode belonging to a larger field, nature tourism, a booming tourist type today by the increase of tourists interested in its activities. Therefore, this paper takes from this concept to below detail the types that are part of it, and finally it does an analysis of the active tourism offer of the Spanish territory, territory that is appropriate for this type of activity.